Selected Elements of the Infrastructure of Polish National Parks from 2005 to 2015 - Bera, Milena; Zaremba, Aneta (Studia Ecologiae et Bioethicae, 2021)
National parks are a very attractive area for tourists. Millions of tourists come there every year, and their number is still growing. This causes many problems in managing the protected area. Therefore, it is important to provide adequate infrastructure and prepare tourist routes in these areas in order to harm nature as little as possible. The aim of the article is to characterize and evaluate the tourist and recreational development of national parks in Poland in the years 2005‒2015. On the basis of the collected empirical data from the Central Statistical Office a comparison was made of selected elements influencing the development and adaptation of a given area of a national park to tourist traffic. A comparative analysis showed the diversity of the studied parks in the discussed scope. The research shows that campsites and bivouacs had the largest share in the accommodation base in national parks, with a noticeable downward trend in each analyzed year. The number of resorts and holiday homes also decreased slightly. On the other hand, between 2005 and 2015 there is an upward trend in the density and length of trails, pistes, and rain shelters.